Prolonged Exposure to Monosodium Glutamate in Healthy Young Adults Decreases Perceived Umami Taste and Diminishes Appetite for Savory Foods. Issue 6 (23rd May 2018) - Noel, Corinna A; Finlayson, Graham; Dando, Robin
Abstract: Background: Research suggests that increased consumption of sweet, salt, or fat is associated with diminished perceived taste intensity and shifted preferences for the respective stimulus. It is unknown whether a similar effect occurs with the consumption of umami. Objective: The aim of the study was to investigate the influence of habitual exposure to umami stimuli on umami taste perception, hedonics, and satiety. Methods: Fifty-eight healthy men ( n  = 16) and women ( n  = 42) participated in a parallel-group, randomized controlled study. The normal-weight [mean ± SD body mass index (kg/m 2 ): 21.8 ± 2.2] group of young adults (mean ± SD age: 22.7 ± 6.2 y) consumed vegetable broth daily for 4 wk. The broth for the treatment group ( n  = 28) was supplemented with 3.8 g monosodium glutamate (MSG), whereas the control group ( n  = 30) consumed a sodium-matched broth without MSG. Perceived umami taste intensity and discrimination in MSG solutions; liking, wanting, and preference of a variety of umami-rich foods; satiation and satiety from an ad libitum meal; and anthropometric measures were evaluated at baseline and at week 4. General linear models assessed the effect of treatment on change from baseline for all outcomes and tested for effect modification of sex. Results: Relative to controls, increased consumption of MSG for 4 wk diminished umami taste in women (8.4 units on generalized Labeled Magnitude Scale; 95% CI: –13.8, –3.1 units; P  = 0.013). The desire for and intake of savory foods decreased after MSG treatment in both sexes with an ad libitum meal (desire: –7.7 units; 95% CI: –13.7, –1.7 units; P  = 0.04; intake: –36 g; 95% CI: –91, 19 g; P  = 0.04). Conclusion: Our results highlight that a month-long diet high in umami stimuli attenuates perceived umami taste and appetite for savory foods in a young, healthy population. Our findings contribute to the understanding of food choice, a factor in the development and maintenance of obesity, as well as the etiology of protein-related health conditions such as osteoporosis and kidney disease. This study is registered at www.clinicaltrials.gov as NCT03010930.